Kedudukan Pancasila Dalam Sumber Segala Sumber Hukum - Mhd Ferdiwansyah; Achmad Zulfikar Siregar (Jurnal Sosial Politik dan Hukum, 2024)
Pancasila as the source of all legal sources has gained juridical legitimacy through TAP MPR Number XX / MPR / 1966 concerning the Momerendum DPR-GR concerning the source of legal order of the Republic of Indonesia and the order of the laws and regulations of the Republic of Indonesia. After the reform, the existence of pancasila was reaffirmed in Law Number 12 of 2011 concerning laws and regulations. Pancasila as the source of all sources of law means that the national legal system must dutch pancasila. However, the existence of the pancaila is increasingly eroded in the national legal system. This is based on several factors, namely: the resistance to the New Order which uses pancasila as a tool for the perpetuation of authoritarian power. The strengthening of pluralism makes contradictions or disharmonization arise in law. Pancasila is also often only used as a symbol of law. For this reason, efforts need to be made to implement pancasila as the source of all laws in the national legal system, namely: making pancasila a legal view so that there are no more legal contradictions due to the application of legal pluralism. Pancasila must have a position as the top of laws and regulations so that pancasila has binding power against all types of laws and regulations so that it does not violate the principle of lex superiori derogate legi inferiori.